Controlling the Conversion of Rice Fields Through the Designation of Protected Rice Fields (LSD) - Mutia Azizah Aksan; Aprila Niravita (Faculty of Law, Universitas Negeri Semarang, 2024)
Law creates justice and benefits in people's lives, its existence is actually realized by the existence of legal certainty so that people can always obey and comply with the law. For example, the legal existence of controlling the conversion of paddy fields through Protected Paddy Lands (LSD) is very important in maintaining and maintaining the availability of paddy fields, this stems from the phenomenon of high levels of conversion of paddy fields causing the area of paddy fields to shrink, reducing the availability of basic necessities. food in the form of rice. With this phenomenon, control over the conversion of LSD rice fields is questionable, especially in the face of discrepancies in LSD determination with the Regional Spatial Planning (RTRW). So this journal was created with the aim of knowing the control over the conversion of paddy fields through LSD and also legal certainty. The results and conclusions in this research study can basically be explained that controlling the conversion of paddy fields through LSD by doing 2 things, namely, 1) LSD conversion and 2) LSD incentives. However, regarding the legal certainty of controlling the conversion of paddy fields through LSD, it is stated that it does not fully contain legal certainty, this is due to an error in determining the LSD in Ministerial Decree No. 1589/SK-HK.02.01/XII/2021. Therefore, it is undeniable that LSD needs to reform and perfect its legal policies so that the goal of controlling the conversion of paddy fields through LSD can be achieved and realized.